We ought to be here: Historicizing space and mobilization in Tahrir Square. (July 2015) - Said, Atef
This article explores the role of space in social movements, through an examination of the case of Tahrir Square in the Egyptian revolution of 2011. The author argues that the pre-existing, historically specific understanding of Tahrir Square as a politicized space of protest drew people there in January 2011 and shaped their participation in the revolution. Specifically, the author suggests that earlier mobilizations that took place in Tahrir Square contributed to the events of the revolution in three ways: (1) provided protesters with an idea about Tahrir as a target of protests, (2) provided protesters with the idea of occupation of Tahrir, and (3) provided protesters with an inspiration in the revolution. The article contributes to the literature in sociology of space and social movements by proposing that the history of space in social movements and previous mobilization matters, but also these may shape the new movement and the role of space in protest. This article is part of the author's research about the Egyptian revolution of 2011. It is based on two phases of historical and ethnographic research in Egypt conducted in 2011 and 2012.